Atividade de Forrageamento de Formigas (Hymenoptera: Formicidae) em Áreas de Mata e Campo de Gramíneas no Pantanal sul-mato-grossense. - Sant'Ana, Michelle Viscardi; Trindade, Rose Benedita Rodrigues; Lopes, Cássia Cristina dos Santos; Faccenda, Odival; Fernandes, Wedson Desidério (EntomoBrasilis, 2008)
O principal objetivo do estudo foi avaliar a taxa de exploração de iscas vivas por formigas em um Ambiente de Mata e de Campo de Gramíneas. O experimento foi desenvolvido no Pantanal sul-mato-grossense, no Município de Corumbá, MS, no período de outubro a novembro de 2006. Cupins do gênero Nasutitermes, serviram de iscas. Em cada área, 80 indivíduos dessa espécie permaneceram expostos no solo sobre uma base de papel filtro durante 10 Minutos. Observou-se a presença de 15 morfoespécies pertencentes a seis gêneros e cinco subfamílias, sendo mais freqüente Myrmicinae. No campo de gramíneas ocorreram maior riqueza e diversidade de espécies. Wasmania sp.1 foi responsável pelo maior número de iscas removidas na Mata e Dorymyrmex sp. 1 no Campo de Gramíneas. A diferença no tempo médio para remoção das iscas nas duas áreas (mata e gramínea) não foi significativa. Das 160 iscas oferecidas durante o experimento, 115 sofreram atacadas por formigas: 69 na mata e 46 no campo de gramínea. Activity of Ants (Hymenoptera: Formicidae) Foraging in a Forest Patch and in a subtropical seasonally flooded lowland grassland in the Pantanal from Mato Grosso do Sul, Brazil. Abstract. The main goal of this research was to evaluate the exploitation rate of live baits for ants in an environment of forest patches and subtropical seasonally flooded lowland grassland. The samples were collected from October to November 2006 in the Pantanal, sub-regions Miranda and Abobral, municipality of Corumbá, Mato Grosso do Sul, Center West Brazil. Termites of the genera Nasutitermes were used as bait, and remained exposed for 10 minutes on the soil. Eighty baits were used in each environment. Fifteen ant morphospecies in six genera and five subfamilies were collected, and the Myrmicinae were the most frequent subfamily. We found larger richness and diversity of species in the subtropical seasonally flooded lowland grassland. Wasmania sp.1 was responsible for the largest number of removed baits (30) in the Forest Patch and Dorymyrmex sp. 1 in the subtropical seasonally flooded lowland grassland. The difference in the average time for removal of the baits from the two areas was not significant. From the 160 baits offered during the experiment, 115 were attacked by ants, 69 in the Forest Patch and 46 in the grassland.